Urban Renewal, Rehabilitation, and Remodelling of Santiago, Chile - de Ramón, Armando; Larráin, José (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
We study the history of the changes in Santiago, Chile, between 1780 and 1880 to verify the stages of urban renewal and the role of state and private investment in the processes. We find that before 1780 the dominant characteristic is conservation, i.e., repair or rebuilding of existing stock of buildings. Between 1780 and 1880 the stages were habilitation, rehabilitation, and remodelling of buildings and spaces for optimum use of urban land. Involved also were more intensive use and the creation of better and more expeditious communication to knit the various quarters of the city together and to provide communication with surrounding entities, such as the port and centres of supply. These stages and developments may follow each other but also may occur in superimposed rhythm. In the earlier years, state investment in new infrastructure is paramount; that investment, in turn, leads both to the development of new quarters and the entrance of private investors who profit from the unearned increment brought about by the state investment.